AMRUTIKARANA - A CRITICAL REVIEW - T.V.Shalini; Jain, Smitha; Nagaraja, T.N. (International Journal of Ayurveda and Pharma Research, 2015)
The Bhasmas are the unique preparations of metals and minerals commonly used in Ayurveda for the treatment of various ailments. Marana (incineration) process converts the native form of metal and minerals into stable and assimilable form called Bhasmas (calx). Bhasmas are said to be the most ancient application of nanomedicine. After the Marana process Bhasmas of Abhraka, Louha and Tamra are subjected to a special process called Amrutikarana. The process is performed to remove the remnant Doshas (impurities) which might be present in the Bhasma and also claimed that it enhances the therapeutic efficacy. In the present paper, an attempt is made to review and put forth the concept of Amrutikarana.